Migrações internacionais em tempos de crise: um estudo sobre o processo de integração dos refugiados sírios na cidade de São Paulo (BRA). - Alexandre Coelho Ferreira (2021)
The Civil War that began in 2011 in the Syrian Arab Republic and remains unfinished has led, by the end of 2020, more than 13 million people to flee their homes, of which 6.8 million have crossed the country's international borders and are in refugee condition, according to data from the United Nations High Commissioner for Refugees (UNHCR). Facing this Syrianmobility , Brazil stands out in the Latin American scenario as the main destination, with a total of more than 3,500 people of this nationality, making it the second largest group of refugees in the country, behind only Venezuelans. However, little is known about the lives of these people in Brazil: how they perform in terms of employment and housing; whether and how they access the health and educational systems; and how they relate to society. Considering the importance of the topic in the current global context and the little knowledge that still exists about the living conditions of this population in Brazil, this paper aims to analyze the integration process of Syrian refugees in the city of São Paulo based on two dimensions: an institutional one, which encompasses the subfields of integration in the labor market, education, health and housing; and a sociocultural one, represented by the subfields of social contact, cultural openness and facilitators of the integration process. To this end, a "Refugee Integration Model" was applied, something unprecedented in the academic production on the subject in the country. The development of the model includes a theoretical debate that allowed the conceptual elaboration of the model and the selection of 89 indicators to guide the analysis and the discussions in each sub-field of integration, divided into legal, objective and subjective indicators. In addition, 32 surveys were applied with refugees and 20 semi-structured interviews were conducted with refugees and stakeholders in the city of São Paulo; as well as secondary sources were analyzed, such as administrative records and legislation related to the rights of refugees and immigrants in the country and in the city of São Paulo. The results indicate that Syrian refugees face significant challenges to integrate institutionally, especially in the areas of employment, education, and housing, and that the influences in one subfield, whether positive or negative, may be directly reflected on the integration in the other. In turn, from the point of view of sociocultural integration, although limitations have also been observed, especially in relation to learning Portuguese, refugees seem to be progressing in this dimension, a result, above all, of the excellent relationship identified between Brazilians and Syrians.